the artikel Tingkat Keterampilan Dasar Renang Anak Usia Prasekolah di NCL Aquatic Surabaya: Tingkat Keterampilan Dasar Renang Anak Usia Prasekolah di NCL Aquatic Surabaya - Qhofifil Aien Tsasyahroh; Muhammad Dzul Fikri; Mokhamad Nur Bawono; Aprilyan Putra Bimantoro (Universitas Hamzanwadi, 2026)
The assessment of swimming skills in preschool children in non-formal institutions is often subjective, requiring an objective and measurable evaluation approach. This study aims to describe the basic swimming skills of preschool children at NCL Aquatic Surabaya using a standardized observation instrument. This quantitative descriptive study involved six children aged 4-6 years as subjects. Data collection was conducted through direct observation using an observation sheet covering seven aspects of basic swimming skills. The data were analyzed descriptively by calculating the mean and standard deviation and categorizing the total scores into three levels of ability. The results showed that two children (33.3%) were in the Good category and four children (66.7%) were in the Moderate category. Arm movements received the highest average score (3.67), while water familiarization, entering the pool, and movement combinations received the lowest scores (3.33). In conclusion, the basic swimming skill level of preschool children at NCL Aquatic Surabaya was generally in the Moderate category, and more focused training is needed on aspects that require adaptation to the aquatic environment and complex movement coordination.